KAJIAN TINGKAT KERENTANAN BANGUNAN TERHADAP TSUNAMI DENGAN METODE BTV (STUDI KASUS PADA DESA KUTA PADANG, KABUPATEN ACEH BARAT) - Dian Febrianti; Meylis Safriani (Universitas Teuku Umar, 2016)
Meulaboh town is one of the areas affected by the tsunami with very severe category apart from Banda Aceh, Calang and Teunom. The tsunami devastated most of the social life and infrastructure the city of Meulaboh. Nowadays, after the tsunami struck there Meulaboh residents who reside in the area close to the sea, such as the residents of Kuta Padang village In fact, all the coastal areas prone Meulaboh an area affected by the tsunami. To minimize the impact of the damage caused by the tsunami hazard, it is necessary to tsunami disaster mitigation efforts with the analysis of the vulnerability of buildings to the tsunami in an area. The purpose of this study is to inform the public and local authorities about the vulnerability of homes to tsunami waves that can destroy homes and buildings. The object of this research is in the village of Kuta Padang, Johan Pahlawan sub-district. This research method by collecting secondary data and conducting surveys and conducted interviews with society who lived in the village. Analyzed using the Buildings Tsunami Vulnerability (BTV). From the results obtained indicate that the region Seulawah has an average value of vulnerability very highest, 95.65%, and 69.57% and 56.52%. Areas that have the lowest susceptibility value is Hamlet Singgah Mata by level of vulnerability value of 60.87% and 47.83% and 34.78%. For evacuation routes, Geurute and Singgah Mata village is the most suitable for the people of Kuta Padang to shelter in case of a tsunami.